Hvordan har netbrugernes præference for forskellige emnespecifikke ordbøger ændret sig i perioden 2006-2014? - Hansen, Poul (Nordiske Studier i Leksikografi, 2018)
The demand for 38 bilingual Danish/Swedish online dictionaries in the period 2006-2014 was statistically investigated. The results show that demand often varies with characteristic patterns in time and space. However, there are indications of a downward trend in user take-up and engagement. In future, more methods may be required to reach out to the users.